Etymology Of Some Terms and Concepts Belong to Religious Tourism - Turayeva Zarnigor Mamarasulovna; Turaev Kuvonchbek Tohirovich (Zien Journals, 2021)
The article gives examples of some terms and concepts related to types of tourism, including religious tourism, such as the origin of the term pilgrimage, religious, excursion, travel, religious research, language, history, content, definition and etymology
Keywords: Tourism; religious tourism; excursion; religious research